Reliability of Critical Fitness Tests for Police Officers - João Daniel Freitas; Sérgio Antunes Ramos; Luís Miguel Massuça (Applied Sciences)
Police officers in training (cadets and provisional officers) are the population most tested in fitness attributes compared to police officers already in operational service. As such, this study aims (i) to validate a fitness assessment protocol for police officers, and (ii) to confirm the effect of sex on fitness performance. In this methodological study, 122 cadets from the Portuguese Police Academy participated and carried out the fitness protocol (horizontal jump, handgrip strength, 60 s of sit-ups, and 20 m shuttle run tests) in two moments (test–retest), separated by one week (seven days). Complementarily, the results of the first assessment were used to study the effect of sex on fitness performance. Superior fitness performances were observed on the retest, with an intraclass correlation coefficient of 0.89 and a standard error of the mean of 0.45 in the fitness assessment protocol and significantly higher values (in all fitness assessments) in male participants. In conclusion, the fitness assessment protocol achieved high reliability in terms of reproducibility (which indicates that it is a valid and reliable protocol), and the influence of sex on the police officers’ fitness profile was confirmed.